Assessing the investment climate to promote a circular bioeconomy: a comparison of 15 countries in the Global South - Taron, Avinandan; Sathiskumar, Abinaya; Malviya, T.; Bodach, Susanne; Muthuswamy, S.; Gebrezgabher, Solomie A. (International Water Management Institute, 2024)
Transitioning towards a circular economy requires investments in new businesses and for this, a supportive environment and business models that can attract private entities are needed. Operating in countries where the enabling factors are minimal or weak proves extremely challenging for private enterprises. The present cross-country study tried to assess the investment climate for promoting a circular bioeconomy, i.e., businesses or public-private partnerships based on organic (municipal) waste. The main indicators used for the assessment are existing regulatory frameworks; business climate and associated procedures; governance in provision of infrastructure; incentives; access to finance; and entrepreneurial ecosystems. While most of the countries analyzed indicated evidence of regulations on waste management and policies related to promoting circularity, the divide is mainly on aspects related to business environments, access to finance and governance. The World Bank’s Ease of Doing Business index and Global Competitiveness Index (GCI) indicate that Southeast Asian and Latin American countries are better positioned than most other Asian and African countries. National economies are challenged by these barriers that need to be addressed to foster the widespread adoption of a more circular bioeconomy.